Pengaruh Word Of Mouth, Image dan Hedonic Shopping Motivation Terhaap Keputusan Pembelian Sepatu Vans ( Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang - Moh Fadillah; Budi Wahono; M. Khoirul Anwarudin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The rapid development of the business world, competition between companies to be able to market their products and services is also getting higher. In this case, every company must have various strategies, one of which is doing Word Of Mouth, Image and Hedonic Shopping Motivation. Because the existence of a good word of mouth can cause consumers to feel satisfied so that they form positive information and then inform others with effective and attractive hedonic shopping motivation and can improve purchasing decisions. The purpose of this study was to determine the effect of doing Word Of Mouth, Image and Hedonic Shopping Motivation on Purchasing Decisions. The selection of the sample in this study used purposive sampling with the criteria of being an active student at the Islamic University of Malang, owning and using Vans shoes. Based on the criteria, 75 respondents were sampled. Data analysis techniques used in this study were descriptive statistical analysis, data instrument testing, classical assumption testing, multiple linear regression analysis, hypothesis testing, model fit testing. The results of the analysis show that Word Of Mouth, Image and Hedonic Shopping Motivation simultaneously influence purchasing decisions. Keywords: Influence Of Word Of Mouth, Brand Image, And Hedonic Shopping.